2021
DOI: 10.51253/pafmj.v71i4.2987
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Generalized Anxiety Disorders in Patients With Polycystic Ovarian Syndrome

Abstract: Objective: To determine the factors associated with generalized anxiety disorders in patients presenting with polycystic ovarian syndrome. Study Design: Cross-sectional study. Place and Duration of Study: Gynecology and Psychiatric outpatient department of Pakistan Institute of Medical Sciences, SZABMU, Islamabad, from Jan to Jul 2016. Methodology: Patients presenting with polycystic ovarian syndrome were enrolled. Patients were selected from the gynaecological and Medicine department. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A study from Singapore showed that BMI was significantly higher in PCOS cases as compared to controls (p < 0.001) [15]. On the contrary, a study on medical students in Pakistan showed that more than 60% of PCOS cases had a normal BMI [16]. However, the link of obesity with PCOS is already established and is believed to be driven by various genetic and metabolic mechanisms [17].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Singapore showed that BMI was significantly higher in PCOS cases as compared to controls (p < 0.001) [15]. On the contrary, a study on medical students in Pakistan showed that more than 60% of PCOS cases had a normal BMI [16]. However, the link of obesity with PCOS is already established and is believed to be driven by various genetic and metabolic mechanisms [17].…”
Section: Discussionmentioning
confidence: 99%